Reproductive biology of the Green Barb, Puntius chola (Hamilton) (Cypriniformes: Cyprinidae) from the Kangsa River, Netrakona, Bangladesh - Saha, Bimal Kanta; Saha, Aparna (Journal of the Asiatic Society of Bangladesh, Science, 2013)
An investigation was conducted on gonadal maturation and fecundity of the Green barb, Puntius chola (Hamilton) over a period of one year from January to December 2006.The overall fecundity was recorded as 1,184.73 ± 1,117.35. Relationships between fecundity and other body parameters were found to be linear, positive and highly significant. Five methods were applied to determine gonadal maturation. The overall GSI level was recorded as 7.05 ± 4.95. The overall GLI level was recorded as 30.43 ± 10.41.The overall percentage of gravid females was calculated as 90.47 ± 16.18. The average ova diameter was determined as 0.44 ± 0.22 mm. The colour of ovary of the Green barb was found to be orange from April to July and September. The monsoon (April to July) and pre winter (September) were found to be the spawning season of the Green barb. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15615 J. Asiat. Soc. Bangladesh, Sci. 38(2): 237-245, December 2012